Komitmen Pernikahan dan Perjodohan Perempuan Usia Dewasa Tengah - Lailatus Solikhah; Fattah Hanurawan (Flourishing Journal, 2021)
The aim research is revealing in depth the description of the phenomenon marital commitment and arranged marriage in the middle-aged woman. Used a type of qualitative method with a descriptive research model. This research was carried out in the Regency of Lamongan with a total of 3 middle-aged women’s who get married because of an arranged marriage and has a marriage of at least 10 years. As the result, the conclusions of the description of marital commitment of arranged marriage in the middle-aged woman that level commitment is high. The type of arranged marriages is planned type and joint venture type. Penelitian ini bertujuan mengungkap secara mendalam deskripsi komitmen pernikahan dan perjodohan perempuan usia dewasa tengah. Menggunakan jenis metode kualitatif dengan model penelitian deskriptif. Penelitian ini dilaksanakan di Kabupaten Lamongan dengan jumlah subjek 3 orang perempuan dewasa tengah yang menikah karena dijodohkan dan memiliki umur pernikahan minimal 10 tahun. Hasilnya, diperoleh kesimpulan gambaran komitmen pernikahan dan perjodohan perempuan usia dewasa tengah tergolong tinggi. Perjodohan yang terjadi yaitu tipe direncanakan dan tipe joint venture.